‘So what about the stories?’ An exploratory study of the definition, use, and function of Narrative Child Sexual Exploitation Material - Crookes, Rebecca L. (Psychology, crime & law, 2017)
The legal and psychological research surrounding online Child Sexual Exploitation Material (CSEM) is focused on visual depictions of children, either as still images or movies. Narrative CSEM (N-CSEM) describes an under-researched area, resulting from difficulties surrounding its conceptualisation, both legally as well as concerning the function for its users. The current study describes an initial attempt in defining N-CSEM in comparison to visual material, based on interviews with users of CSEM and N-CSEM and professionals working with this user group. Thematic Analysis resulted in three super-ordinate themes. All themes were analysed and enriched from the perspectives of user- and service-representatives. The study provides insight into N-CSEM as a separate entity from visual CSEM, challenging and informing legal decision-making and assessment and treatment providers for users of CSEM.